2014
DOI: 10.1371/journal.pone.0100676
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Dicer-Independent, Cell-Type Dependent Alternate Targeting Sequence Generator: Implications in Gene Silencing & Pooled RNAi Screens

Abstract: There is an acceptance that plasmid-based delivery of interfering RNA always generates the intended targeting sequences in cells, making it as specific as its synthetic counterpart. However, recent studies have reported on cellular inefficiencies of the former, especially in light of emerging gene discordance at inter-screen level and across formats. Focusing primarily on the TRC plasmid-based shRNA hairpins, we reasoned that alleged specificities were perhaps compromised due to altered processing; resulting i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Interestingly, despite COA producing an increase in Dicer1 in tolerant mice, 14 of the 47 miRNAs significantly altered by COA were down-regulated. The discord between Dicer1 levels and down-regulated miRNAs could reflect Dicer-independent processing (Bhinder et al, 2014 ; Liu et al, 2015 ) that may even give rise to inverse production levels (possibly due to competitive Dicer loading; Liu et al, 2015 ). This point is relevant since we chose to further investigate a miRNA that was down-regulated, namely miR-27a.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, despite COA producing an increase in Dicer1 in tolerant mice, 14 of the 47 miRNAs significantly altered by COA were down-regulated. The discord between Dicer1 levels and down-regulated miRNAs could reflect Dicer-independent processing (Bhinder et al, 2014 ; Liu et al, 2015 ) that may even give rise to inverse production levels (possibly due to competitive Dicer loading; Liu et al, 2015 ). This point is relevant since we chose to further investigate a miRNA that was down-regulated, namely miR-27a.…”
Section: Discussionmentioning
confidence: 99%
“…The role of individual AGO proteins (AGO 1, 2, and 3) and their specificity for certain miRNAs, mRNAs, or miRNA/mRNA combinations is under scrutiny. Further, the role of AGO2 and even Dicer in miRNA processing is still under analysis (Bhinder et al., ; Cheloufi et al., ). Studies in AGO2 or Dicer‐deficient cells or mice revealed that miRNA processing independent of these molecules is possible but regulation of specific mRNAs can be impaired (Bhinder et al., ; Levy et al., ).…”
Section: Microrna Processing Defectsmentioning
confidence: 99%
“…Further, the role of AGO2 and even Dicer in miRNA processing is still under analysis (Bhinder et al., ; Cheloufi et al., ). Studies in AGO2 or Dicer‐deficient cells or mice revealed that miRNA processing independent of these molecules is possible but regulation of specific mRNAs can be impaired (Bhinder et al., ; Levy et al., ). Interestingly, depletion of DGCR8 was recently linked to stem cell phenotype, cellular reprogramming and differentiation in keratinocytes further supporting a role of miRNA processing proteins in cancer development (Chakravarti et al., ).…”
Section: Microrna Processing Defectsmentioning
confidence: 99%
“…This is because shRNAs against multiple unintended targets can be generated by alternate transcriptional start sites within lentiviral shRNA constructs. 48 This phenomenon may have a significant contribution to the low confirmation rates in shRNA screens and the relatively low cross-validation rate between shRNA and siRNA screens. [49][50][51] Given these issues, researchers in the CRISPR/Cas9 field have invested significant efforts in the determination of OTE and their mitigation.…”
Section: Dealing With Otementioning
confidence: 99%